Numerical simulation of dynamic response and failure of large-diameter thin-walled cylinder under vibratory penetration. (1st April 2022) - Lu, W.J.; Li, B.; Li, J.H.; Hou, J.F.; Xu, X.W.; Zhang, L.M.
Abstract: Large-diameter thin-walled steel cylinders, which were first used in the Hong Kong-Zhuhai-Macao Bridge project as an enclosure structure for artificial islands, have been applied in many large-scale offshore projects. The thin-walled steel cylinder may fail during vibratory penetration in certain conditions such as asynchronicity of hammers and presence of corestones or sloping rockhead, which cannot be accommodated in routine wave equation analysis. This study aims to further develop the novel thin-walled offshore retaining structure. A three-dimensional (3D) finite element model is established to simulate the penetration of large-diameter thin-walled steel cylinders using a group of vibratory hammers. The dynamic response of the steel cylinder under multi-point vibrations is sensitive to penetration depth, vibration amplitude, and frequency. Failure under unsynchronized vibrations occurs first at the free part of the cylinder above the ground level. A "shearing" failure mode can develop when the asynchronous hammers cluster together and a "shearing-compressive" failure mode can develop when the asynchronous hammers are alternately distributed. Failure of the cylinder in the presence of geological obstacles occurs at the cylinder toe. "Compressive buckling" and "extrusion buckling" failure modes can develop when the steel cylinder encounters a corestone and sloping rockhead, respectively. Highlights: Large-diameter steel cylinders were first used in the Hong Kong-Zhuhai-Macau Bridge project. This study aims to advance this novel offshore structure using 3D dynamic finite element analysis. Dynamic response and failure of the cylinder under multi-point vibratory penetration are analyzed. "Shearing" or "shearing-compressive" failure of the cylinder can occur under asynchronous vibrations. "Compressive buckling" or "extrusion buckling" failure can be caused by geological obstacles.